Fibronectin inhibits osteoclastogenesis while enhancing osteoclast activity via nitric oxide and interleukin-1β-mediated signaling pathways - Gramoun, Azza; Azizi, Natoosha; Sodek, Jaro; Heersche, Johan N.M.; Nakchbandi, Inaam; Manolson, Morris F. (Journal of cellular biochemistry, 2010)
Osteoclasts are bone-resorbing cells formed by fusion of mononuclear precursors. The matrix proteins, fibronectin (FN), vitronectin (VN), and osteopontin (OPN) are implicated in joint destruction and interact with osteoclasts mainly through integrins. To assess the effects of these matrix proteins on osteoclast formation and activity, we used RAW 264.7 (RAW) cells and mouse splenocytes differentiated into osteoclasts on tissue culture polystyrene (TCP) or osteologic™ slides pre-coated with 0.01-20 µg/ml FN, VN, and OPN. At 96 h, osteoclast number and multinucleation were decreased on VN and FN compared to OPN and TCP in both RAW and splenocytes cell cultures. When early differentiation was assessed, VN but not FN decreased cytoplasmic tartrate-resistant acid phosphatase activity and pre-osteoclast number at 48 h. OPN had the opposite effect to FN on osteoclast formation. When RAW cells were differentiated on OPN and treated by FN and OPN, osteoclast number only in the FN treated group was 40-60% lower than the control, while the total number of nuclei was unchanged, suggesting that FN delays osteoclast fusion. In contrast to its inhibitory effect on osteoclastogenesis, FN increased resorption by increasing both osteoclast activity and the percentage of resorbing osteoclasts. This was accompanied by an increase in nitric oxide (NO) levels and interleukin-1β (IL-1β). IL-1β production was inhibited using the NO-synthase inhibitor only on FN indicating a FN-specific cross-talk between NO and IL-1β signaling pathways. We conclude that FN upregulates osteoclast activity despite inhibiting osteoclast formation and that these effects involve NO and IL-1β signaling. J. Cell. Biochem. 111: 1020-1034, 2010. © 2010 Wiley-Liss, Inc.